1971
DOI: 10.1159/000155373
|View full text |Cite
|
Sign up to set email alerts
|

Hydronephrosis of Pregnancy: a Naturally Occurring Disorder in Non-human Primates Closely Resembling that in Man

Abstract: Several species of Old World monkeys, and the chimpanzee are shown to exhibit ureteral dilatation during pregnancy similar to human hydronephrosis of pregnancy. The entity is probably due to ureteral obstruction by the gravid uterus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1973
1973
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 3 publications
(3 reference statements)
1
0
0
Order By: Relevance
“…Travis and Holmes (1974) reported a linear increase in water consumption from the day of conception through GD 138, with a correlative significant increase in mean daily urine output. Evaluation of four species of nonhuman primates (M. mulatta, M. speciosa, E. patas, and P. troglodytes) showed that significant upper ureteral dilatation occurs during pregnancy, similar to findings in humans (Roberts and Wolf, 1971). (Chambers and Hearn, 1985).…”
Section: Maternal Changes With Pregnancysupporting
confidence: 64%
“…Travis and Holmes (1974) reported a linear increase in water consumption from the day of conception through GD 138, with a correlative significant increase in mean daily urine output. Evaluation of four species of nonhuman primates (M. mulatta, M. speciosa, E. patas, and P. troglodytes) showed that significant upper ureteral dilatation occurs during pregnancy, similar to findings in humans (Roberts and Wolf, 1971). (Chambers and Hearn, 1985).…”
Section: Maternal Changes With Pregnancysupporting
confidence: 64%